1994
DOI: 10.2307/2410246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal and Paternal Environment and Genotype on Offspring Phenotype in Solidago altissima L.

Abstract: To predict the possible evolutionary response of a plant species to a new environment, it is necessary to separate genetic from environmental sources of phenotypic variation. In a case study of the invader Solidago altissima, the influences of several kinds of parental effects and of direct inheritance and environment on offspring phenotype were separated. Fifteen genotypes were crossed in three 5 x 5 diallels excluding selfs. Clonal replicates of the parental genotypes were grown in two environments such that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
164
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(173 citation statements)
references
References 75 publications
8
164
0
1
Order By: Relevance
“…Empty seeds or seeds with desiccated embryos are found in hybrid tea roses, in which germination capacity is also related to seed density ). These results are in agreement with the general knowledge of predominant maternal influence on seed development, germination and early seedling growth in plants (Roach and Wulff 1987;Schmid and Dolt 1994;Thiede 1998). Our crossings were not performed as a full diallel scheme, and therefore the maternal effect cannot be excluded.…”
Section: Discussionsupporting
confidence: 92%
“…Empty seeds or seeds with desiccated embryos are found in hybrid tea roses, in which germination capacity is also related to seed density ). These results are in agreement with the general knowledge of predominant maternal influence on seed development, germination and early seedling growth in plants (Roach and Wulff 1987;Schmid and Dolt 1994;Thiede 1998). Our crossings were not performed as a full diallel scheme, and therefore the maternal effect cannot be excluded.…”
Section: Discussionsupporting
confidence: 92%
“…in Carex (Table 4). Another possible explanation for the observed effects could be attributed to maternal environmental carry-over effects via the seeds (Schmitt et al 1992;Schmid and Dolt 1994). However, this explanation is unlikely since mean seed mass did not differ between the three habitat island types and the results never changed when we included seed mass as a covariable in the analyses.…”
Section: Discussionmentioning
confidence: 98%
“…This indicates that there is considerable quantitative genetic differentiation among plants of M. guttatus from populations with annual and perennial life-cycles in important life-history traits and their plasticities. An alternative explanation could be that differences among the life-cycle categories are a consequence of maternal environmental carry-over effects through seeds (Schmid and Dolt 1994;Weiner et al 1997). Galloway (1995) suggested that maternal environmental carry-over effects may affect phenology and sexual and vegetative reproduction of M. guttatus through effects on seedling size.…”
Section: Discussionmentioning
confidence: 99%